Pemberian Promosi Kesehatan Pada Anak Sekolah Melalui Gamification Berbasis Android: Studi Literatur - Anggraini Marissa; Sigit Mulyono (Universitas Lampung, 2023)
Promotion Of Health to School Children Through Android-Based Gamification: Literature Review. Health Promotion is one of the strategies to maintain and improve health status through changes in healthy living behavior. The implementation of health promotion must be able to keep up with the development of technology and information that continues to develop, as well as respond to public health needs through media that are easy to access by related health promotion targets. Gamification is one of the media developed in the implementation of health promotion in the form of games that are packaged as attractively as possible according to the age target of the expected health information. School children are the target group for health promotion through gamification as a form of special nursing intervention in accordance with the growth and development of age and social issues that continue to develop. Presented as attractively as possible and so that the information conveyed can be accepted, there is motivation so that the expected behavior change occurs. Keywords: Gamification, health promotion, school age